Introduction and use of plants of the species of the genus Physalis L. in Ukraine - О. П. Бондарчук; О. М. Вергун; В. В. Фіщенко; Д. Б. Рахметов (Plant Varieties Studying and Protection)
Purpose. Development of scientific and applied foundations for the introduction, selection and use of plants of the species of the genus Physalis L. to ensure food security in Ukraine.